CONFERENCE REPORT: The Migration Conference 2017 Athens, August 23-26, 2017 Harokopio University - de Freitas Castro, Emília Lana; Sözen, Ülkü Sezgi (Border Crossing, 2017)
According to the UN, in 2015 the number of international migrants was estimated on 244 million, which means that 3,3 percent of the world's population is on the move or live in a country other than his/her country of birth/origin. Globally, in 2014, the number of refugees was estimated approximately 20 million, which has been increasing since the so-called "refugee crisis" has started. This increase in the number of movers called attention to migration studies and approached the issue from a different perspective, under an international and interdisciplinary point of view. Therefore, the 5th edition of The Migration Conference has been organized in a fully inclusive way, bringing about 500 scholars, researches, representatives of policy making bodies, media, and NGOs all around the world together in Athens, Greece. The 6th edition of The Migration Conference in June 2018 at the University of Lisbon is expected to continue this tradition.